2009
DOI: 10.1007/s11256-009-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Talking About Ourselves, Talking About Our Mothers: Latina Prospective Teachers Narrate Their Life Experiences

Abstract: Through a Bakhtinian conceptual framework, this text explores Latina prospective teachers' life histories-their experiences at home, in their K-12 schooling, on campus in a Midwestern university, and in their teacher education program. Further, it shows how often, when asked about their own experiences, Latinas responded with stories of their mothers' past and present experiences. The author shows how drawing on stories of their mothers supported young women in rebutting discourses promulgated by white female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Like Mishler (2004), we have found that in talking about their lives, participants frequently illustrate points they wish to make in storied form (see Gomez, Rodriguez, & Agosto 2008a;Gomez, Rodriguez, & Agosto, 2008b;Gomez, 2010) and that these stories enabled them to talk about their experiences and how they understand them. As Mishler argues (1990), "I take it for granted that the account produced is a reconstruction of the past, shaped by the particular context of its telling" (p. 427).…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…Like Mishler (2004), we have found that in talking about their lives, participants frequently illustrate points they wish to make in storied form (see Gomez, Rodriguez, & Agosto 2008a;Gomez, Rodriguez, & Agosto, 2008b;Gomez, 2010) and that these stories enabled them to talk about their experiences and how they understand them. As Mishler argues (1990), "I take it for granted that the account produced is a reconstruction of the past, shaped by the particular context of its telling" (p. 427).…”
Section: Methodssupporting
confidence: 52%
“…Mary Louise's research (Gomez, Rodriguez, & Agosto, 2008a;Gomez, Roddriguez, & Agosto, 2008b;Gomez 2010) concerning prospective teachers' beliefs about whom they see as different from themselves as well as that of other researchers from around the globe (Camacho, 2004;Carrington & Sagger, 2008;Carrington, Mercer, Bland, & Kimber, 2010;Carrington & Iyer, 2011;Sharpe & Dear, 2013) lead us to believe that talking and writing about their experiences is an important means of uncovering prejudices and reasons these developed. So, too, do Lutovac and Kassila (2011) from Slovenia and Finland report that narrating their classroom experiences helped prospective Slovenian and Finnish teachers understand how and why they had developed negative feelings about teaching and learning mathematics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This work is an important intervention into understanding the protective factors of POCI families for SGD individuals. Although it is established that mothers and other family members are important role models for POCI youth and adults (Bush, 2000;Collins, 1987;Feinstein et al, 2009;Gomez, 2010;Lawson Bush, 2004;M endez-Morse, 2004) and that family acceptance is a protective factor for SGD youth (Ryan, Russell, Huebner, Diaz, & Sanchez, 2010;Simons, Schrager, Clark, Belzer, & Olson, 2013), the literature on SGD POCI individuals rarely highlights the supportive and protective aspects of POCI families. Black and Latinx SGD family members, especially mothers and othermothers, are more important models for resilience than celebrities and SGD adults, findings that are contrary to existing studies (Bird et al, 2012;Gomillian & Giuliano, 2011;Grossman & D'Augelli, 2004;Johnson & Gastic, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mothers provided models for how to interact with the world and display competence as a woman. In addition, in a study with aspirant Latinx teachers, Gomez (2010) argued that Latinx women use "mother stories" to narrate their own competencies as Latinx woman. Latinx mothers provided their daughters with discourses to rebut mainstream devaluation of Latinx competence.…”
Section: Role Models In Poci Familiesmentioning
confidence: 99%
“…O’Hara and Pritchard (2008), in a finding from a professional development study on diversity, note, “A critical component of any successful teacher preparation program is faculty regularly modeling best practices with respect to instructional strategies for working with diverse student populations” (p. 45). Gomez (2010) argues that we need “. .…”
Section: Review Of the Literaturementioning
confidence: 99%